ANALYSIS OF THERMOELECTRIC POTENTIAL SP1848-27145 SA AS A POWER PLANT WITH UTILIZING THE HEAT ENERGY OF COMBUSTION - Haripuddin, Haripuddin; Irfan, Muhammad; Suhardi, Iwan (Fakultas Teknik Universitas Negeri Makassar, 2023)
This research is experimental and aims to determine the characteristics of the SP1848-27145SA generator thermoelectric module in the form of power generated and its performance as a power plant by utilizing heat energy from a combustion furnace. The method used in testing the thermoelectric characteristics of the generator is a direct experimental method by measuring the output voltage, current, hot side, and cold side of the thermoelectric and the power generated by the module attached to the combustion furnace. Thermoelectric testing of the SP1848-27145 SA generator as a power plant by utilizing heat energy from a combustion furnace with a maximum voltage generated electronic device load of 2.25 Volts at ΔT 46°C and a maximum generated power of 0.09 watt. The thermoelectric performance of the SP1848-27145 SA generator is obtained in three different configurations: single, series, and parallel. The highest thermoelectric power produced is in the series configuration, where the power obtained is 0.25 watts, while the results from the parallel arrangement have the same power value. very small, namely 0.02 watts, and the highest efficiency value only reaches 3.40%.